COMPARISON BETWEEN TRADITIONAL OSTEOSYNTHESIS AND LOCKED PLATES IN LONG FRACTURES OF SMALL ANIMALS (International Seven Journal of Multidisciplinary, 2025)
Objective: To compare the biomechanical and clinical efficacy of traditional osteosynthesis with DCP plates and osteosynthesis with locked plates in the treatment of long fractures in small dogs, highlighting advantages, limitations, and practical applications. Diaphyseal fractures in small animals represent a clinical challenge, requiring techniques that provide stability and respect bone biology. This literature review analyzed experimental and clinical studies comparing traditional dynamic compression (DCP) implants with locked plates, including the S.P.S. Free-Block system and locked intramedullary rods. The literature shows that DCP plates require direct bone-implant compression and are effective in simple fractures, but with a higher risk of vascular interference and failure when poorly applied. Locked plates, on the other hand, allow for less aggressive surgery, preservation of the periosteum, and angular stability, with equivalent or superior biomechanical results. The versatility of these systems, confirmed by studies such as Agurto Merino (2011) and Dias (2009), reinforces their clinical applicability. It is therefore concluded that, although both techniques have their value, locked implants offer greater mechanical and biological safety, especially in unstable, metaphyseal fractures or in fragile bones.